Increase of spinach growth through the use of larger plug cell volume and an exogenous BAP spray - Di Matteo, Javier Antonio (2015)
In spinach, transplanting has replaced direct seeding but small containers may cause root restriction effects that would be decreased post-transplant yield. Although a single hormonal regulator (BAP) spray is effective in overcoming root restriction, the mechanisms involved are unknown. The objective of this work was to analyze yield changes by the use of different plug cell volumes and BAP as foliar spray. Our results showed that the use of large plug cell volumes and BAP sprays at the pre-transplant stage increased plant productivity, through an increase in the relative growth rate (RGR) or the rate of leaf area expansion (RLAE). We found a close direct relationship between RGR and net assimilation rate (NAR) but an inverse relationship between RGR and leaf area ratio (LAR). In addition, we found that NAR significantly increased as leaf thickness, intercellular spaces and stomatal density increased. A change in dry weight partitioning toward shoots was found as well.